Cutaneous Miliary Tuberculosis in a Chronic Kidney Disease Patient - Suraprasit, Pudit (Case Rep Dermatol, 2014)
A 79-year-old Thai woman with advanced renal failure, dyslipidemia and anemia of chronic disease was admitted to hospital with prolonged fever, productive cough and multiple discrete small pustules on her face, trunk and extremities. A chest X-ray revealed diffuse miliary infiltration. Mycobacterium tuberculosis complex DNA was detected by polymerase chain reaction in sputum and scrapings of pustules from her skin. Blood culture identified M. tuberculosis complex. Pulmonary and cutaneous miliary tuberculosis was diagnosed. The patient's symptoms improved after 3 weeks of treatment with isoniazid, rifampicin, ethambutol and pyrazinamide. This report details a case of cutaneous miliary tuberculosis in a non-dialysis chronic kidney disease patient.